2017
DOI: 10.14742/ajet.3505
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting teachers’ technological pedagogical knowledge

Abstract: This paper starts from the understanding that teachers' knowledge is situated, grounded in knowledge derived from formal training and from experiences in practice. Based on this understanding we examine teachers' reasoning in relation to the pedagogical choices teachers make while using ICT in practice. We argue that teachers' reasoning about pedagogy elicits their technological pedagogical knowledge (TPK). Data from 29 video cases show how elementary teachers used ICT to facilitate specific pedagogical strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
1
31
0
2
Order By: Relevance
“…While previous research indicated that the STLDM improves the preservice teachers' self-efficacy for designing lessons and fosters relevant design beliefs, more instructional support can be further integrated. These supports could be instructor modeling of design thinking to avoid early fixation (Razzouk & Shute, 2012), experiential learning among the preservice teachers to foster deep understanding, and reflection and collaboration among the preservice teachers (Heitink et al, 2017;Tondeur et al, 2012).…”
Section: Models To Facilitate Preservice Teachers' Tpack Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous research indicated that the STLDM improves the preservice teachers' self-efficacy for designing lessons and fosters relevant design beliefs, more instructional support can be further integrated. These supports could be instructor modeling of design thinking to avoid early fixation (Razzouk & Shute, 2012), experiential learning among the preservice teachers to foster deep understanding, and reflection and collaboration among the preservice teachers (Heitink et al, 2017;Tondeur et al, 2012).…”
Section: Models To Facilitate Preservice Teachers' Tpack Developmentmentioning
confidence: 99%
“…As with pedagogical content knowledge (PCK), TPACK has emerged to be a powerful notion to unpack the knowledge and skills teachers need to design lessons for 21st century classrooms (Harris, Phillips, Koehler & Rosenberg, 2017). Nonetheless, current research indicates that the emergence of TPACK has not transformed the state of technology integration in classrooms (Heitink, Voogt, Fisser, Verplanken, & van Braak, 2017;Pringle, Dawson, & Ritzhaupt, 2015;Tondeur, Aesaert, et al, 2017). More research on developing teachers' TPACK specifically to promote 21st century competencies through various pathways is needed (Koehler, Mishra, Kereluik, Shin, & Graham, 2014;Valtonen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study of Heitink, et al [10] show that the use of ICT in facilitating learning (student activities, classroom management, mentoring strategies) of the elementary school teachers is very helpful in making the students active.…”
Section: Blended Learningmentioning
confidence: 99%
“…Chai and Koh pointed out that, to a large extent, teachers still focus on replacing teacher-centered teaching in ICT integration, rather than changing teaching methods to support learning in the 21st century [40]. Moreover, many researchers have pointed out that it is difficult for teachers to integrate science and technology into their teaching process [41], resulting in a large number of research reports showing that the expected teaching changes from ICT to teacher-led learning to student-centered learning are still not common in schools [42], [43].…”
Section: A Meaningful Learning For Teaching Professional Developmentmentioning
confidence: 99%